Metallurgical processing of titanium aluminides on industrial scale. (December 2018) - Güther, Volker; Allen, Melissa; Klose, Joachim; Clemens, Helmut
Abstract: Plenty of papers with regard to the processing of TiAl alloys via investment casting, forging, rolling, extrusion pressing as well as mechanical machining have been published, whereas the manufacturing of gamma-TiAl based alloys and corresponding semi-finished products has not been entirely described so far. The aim of this paper is to review and evaluate the present technologies of TiAl alloy production on an industrial scale. Metallurgical alloying techniques such as vacuum arc remelting (VAR), plasma arc melting (PAM) and electron beam melting (EBM) are being shortly described and evaluated with regard to their advantages and disadvantages from both technical and economical point of view. Particular focus is set on some specifics in metallurgical processing of TiAl alloys compared to Ti and Ti alloys. Outstanding requests on the accuracy of chemical composition, microstructural homogeneity, acceptable local deviations of alloying elements, small sizes of the products, and, additionally, the very limited wrought processing capability of TiAl alloys require a set of adjusted metallurgical technologies for the manufacturing of semi-finished products. With this regard, the production of small sized semi-finished parts via skull melting technologies and subsequent centrifugal casting in permanent moulds have been successfully developed and industrialized. Both, VAR skull melting (VAR SM) for ingot conversion and induction skull melting (ISM) for the conversion of valuable revert materials result in technically indistinguishable products due to the application of a consistent centrifugal casting technology. Both procedures offer the highest flexibility on product shapes and dimensions for minimizing the specific materials usage, which has a direct positive influence on final component costs. Resulting materials properties of the semi-finished products meet entirely the different (customer related) specification requirements. There are basically no technical limitations with regard to TiAl alloy compositions as it is the case for TiAl alloy manufacturing via other technologies.